PUBLISHING ACTIVITIES BY MARTYNAS JANKUS BEFORE THE ESTABLISHMENT OF HIS PRINTING HOUSE (1879–1889) - KAUNAS, DOMAS (Knygotyra, 2014)
Martynas Jankus (1858–1946) is a famous worker of Lithuanian press in Prussia, a participant of national movement, a politician who supported bringing together two parts of the Lithuanian nation separated by the borders between German and Russian empires. Over more than 40 years he had published and printed 395 non-periodical and 27 periodical publications in Lithuanian and some in German and Byelorussian languages. Among the authors of these publications, there were many significant representatives of Lithuanian and other nations: writers, ethnologists, historians, Protestant theologians and politicians. Jankus’ personality was formed by the life style of a peasant family, social environment of his native Bitėnai village and the pressure of national discrimination affecting the indigenous people. He attended only a primary school and later self-educated himself by reading voratiously literature about Lithuania and Lithuanians. Lithuanian newspapers and especially the works by Georg Sauerwein, a defender of the interests of small nations in the German empire, published in them have increased his motivation for social activity. The active political movement of the end of the 19th century and the election campaigns to the Prussian Landtag and German Reichstag directly influenced his decision to participate in publishing. In 1879–1888 he published several leaflets in support of Lithuanian candidates, some books, pamphlets and calendars for the cultural education of Lithuanians. Among these publications Jankus included his own collections of original and folk poetry as well as prose translated from German and Polish languages augmented by polemic articles. When Jankus got acquainted with the members of the national movement in Great Lithuania, he became an editor and administrator of the Lithuanian periodical “Auszra” established by them. Other editors stayed on his farm in Bitėnai. As there was a lack of popular literature,Jankus and his companion published the Lithuanian “Auszra” calendar (“Lietuviškas “Auszros“ kalendorius”) in 1883 and 1884. The texts of educational and applied character were published in the calendar as well as literary texts, such as original and translated poetry and prose. They were written by Lithuanian authors Jonas Basanavičius, Andrius Jonas Vištelis, Petras Vileišis, and writers of other nations such as Sauerwein, Józef Ignac Kraszewski, Adam Mickiewicz, Ivan Krylov, Aleksandr Puškin, William Shakespeare and Guy de Maupasannt. For many Lithuanians these translations were the first acquaintance with the world literature.Martynas Jankus used to order printing of his books, calendars and “Auszra” in the printing houses of nearby towns, such as Ragnit (Lith.: Ragainė) and Tilsit (Lith.: Tilžė). Their production was disseminated in Lithuania Minor and smuggled to the Great Lithuania, which was under the strict ban on Latin printing introduced by the Russian tsarist regime. For this purpose, Jankus established a network of illegal disseminators of literature. It consisted of two sectors: secret book transporters over the border and disseminators in the Great Lithuania and legal storage owners near the border on the side of Prussia. This network was extended along the German-Russian border from Palanga till Dubeningken (Lith.: Dūbininkai; Dubeninki in present day Poland).The first stage of publishing activity was successful for Martynas Jankus. He acquired publishing expertise, knowledge of organizing illegal business, created long-term relations with the owners of printing houses, established the network for the dissemination of publications, developed skills to supply it with different printing materials and information. By March of 1889, the publisher from Bitėnai had established his own printing house in Ragnit and started printing business. This was the start of the second stage of Martynas Jankus’ activity.